The ruthenium-catalyzed meta-selective C–H nitration of various azole ring-substituted arenes. Issue 40 (4th October 2019) - Zhang, Dong; Gao, Di; Cai, Jinlin; Wu, Xiaoyu; Qin, Hong; Qiao, Kai; Liu, Chengkou; Fang, Zheng; Guo, Kai
Abstract : The efficient and gentle ruthenium-catalyzed meta -selective CAr –H nitration of azole ring substituted arenes has been developed. Abstract : The efficient ruthenium-catalyzed meta -selective CAr –H nitration of azole ring substituted arenes has been developed. In this work, Ru3 (CO)12 was used as the catalyst, AgNO2 as the nitro source, HPcy3 + ·BF4 − as the ligand, pivalic acid as the additive, and DCE as the solvent, and a wide spectrum of arenes bearing thiazole, pyrazolyl or removable oxazoline directing groups were tolerated in this meta -selective CAr –H nitration, affording the nitrated products in moderate to good yields. Moreover, this study reveals a gentler and environmentally friendly way to access meta -nitration arenes compared to the traditional process.